Experiment and application of ceramsite concrete used to maintain roadway in coal mine. (November 2020) - Chen, Ying; Hui, Qianjia; Zhang, Hongwei; Zhu, Zhijie; Wang, Cunwen; Zhao, Jian
This paper presents a scientific basis and reference for the application of ceramsite concrete in underground coal mines. Taking fly-ash ceramsite as raw material, a variety of mix proportions of C20 ceramsite concrete were proposed by changing the sand rate of concrete. The results showed that: (1) fly-ash ceramsite has different water absorption performance with different particle sizes. The water absorption stopped after soaked for 48 h. So, the ceramsite should be soaked for more than 48 h to prevent the cement from hydrating insufficient which affects the mechanical properties of the concrete. (2) Seven mix proportions of C20 ceramsite concrete were designed by changing the ceramsite proportion. The ceramsite proportion of 43% was determined as optimal scheme whose 28-day strength was 29.60 MPa and elastic modulus was 12.45 GPa. (3) The optimal scheme was applied and verified in the field. The early strength of ceramsite concrete promotes quickly, 3-day strength was 16.8 MPa, and the 28-day strength was 29.9 MPa. Compared with ordinary pebble concrete, ceramsite concrete can provide faster, higher strength support to the roadway. Meanwhile, ceramsite concrete have properties of lightweight, and its application will bring economic and social benefits.